ANALISIS YURIDIS TENTANG SANKSI PIDANA DALAM TINDAK PIDANA ILLEGAL LOGGING (PUTUSAN NOMOR 294/PID.B/LH/2023/PN BLS): Juridical Analysis of Criminal Sanctions in Illegal Logging Crimes (Decision Number 294/PID.B/LH/2023/PN BLS) - Dionysius Ansel Yuswanto; Ermania Widjajanti (Faculty of Law, Universitas Trisakti, 2025)
Illegal logging in Indonesia threatens forest sustainability and causes significant losses. Law enforcement against offenders often proves ineffective. This study examines whether criminal sanctions imposed by judges align with Article 83 Paragraph (1) letter b in conjunction with Article 12 letter e of Law No. 18 of 2013, as amended by Article 37 of Government Regulation No. 2 of 2022, and whether these sanctions meet the objectives of criminal penalties. Using a normative juridical method and descriptive-analytical approach, the research analyzes secondary data through qualitative methods with deductive logic. The findings show that the criminal sanctions imposed on Sofyan Roman Als Pian Bin Suparno, including a prison sentence of 1 year and 8 months and a fine of IDR 500,000,000, are disproportionate to the damage caused. The punishment fails to achieve objectives such as reformation, restraint, retribution, and deterrence. The study concludes that these sanctions are inadequate andineffective in addressing the harm of illegal logging. It recommends including mandatory forest restoration as part of the penalty to better mitigate the impacts.